2015
DOI: 10.4194/1303-2712-v15_1_04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aimed to evaluate the nutritional qualities of selected commercial fish meals (FM) in diets of juvenile shi drum, Umbrina cirrosa L..The five FMs diets based on two Peruvian anchovy meals (one is a flame dried FM: Peru-1 and the other steam-dried FM: Peru-2), a Danish low-temperature FM (Danish LT), a domestic anchovy LT meal (Domestic LT) and an Alaskan white FM (WFM) as major protein source were formulated to contain 56% protein. The diets were fed to triplicated groups of fish with initial averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…Reproduction without hormonal induction has already been achieved for shi drum born in captivity (Arizcun-Arizcun et al 2014). So far, some studies on its nutritional requirements (Akpinar et al 2012, Morgane and Fountoulaki 2014, Sevgili et al 2015 and on the use of plant sources (soybean and cereals) in its diet (Segato et al 2005(Segato et al , 2008 have showed that the shi drum can tolerate a relatively high inclusion of plant products without having negative effects on growth and feed efficiency. For juvenile meagre (Argyrosomus regius), a sciaenid with similar characteristics to the shi drum, Ribeiro et al (2015) studied the effect of vegetable-based diets on growth, intestinal parameters, and hematological stress indicators over a period of 88 d and found that growth was not significantly affected by the replacement of fish meal and fish oil with the alternative ingredients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduction without hormonal induction has already been achieved for shi drum born in captivity (Arizcun-Arizcun et al 2014). So far, some studies on its nutritional requirements (Akpinar et al 2012, Morgane and Fountoulaki 2014, Sevgili et al 2015 and on the use of plant sources (soybean and cereals) in its diet (Segato et al 2005(Segato et al , 2008 have showed that the shi drum can tolerate a relatively high inclusion of plant products without having negative effects on growth and feed efficiency. For juvenile meagre (Argyrosomus regius), a sciaenid with similar characteristics to the shi drum, Ribeiro et al (2015) studied the effect of vegetable-based diets on growth, intestinal parameters, and hematological stress indicators over a period of 88 d and found that growth was not significantly affected by the replacement of fish meal and fish oil with the alternative ingredients.…”
mentioning
confidence: 99%
“…Ya se ha logrado la reproducción, sin inducción hormonal, de ejemplares de esta especie nacidos en cautividad (Arizcun et al 2014). Hasta ahora, algunos estudios sobre sus necesidades nutricionales (Akpinar et al 2012, Morgane y Fountoulaki 2014, Sevgili et al 2015) y sobre el uso de fuentes vegetales (productos de soya y cereales) en su dieta (Segato et al 2005(Segato et al , 2008 han demostrado que el verrugato tolera una inclusión relativamente alta de productos vegetales sin tener efectos negativos en el crecimiento y la eficiencia alimenticia. En juveniles de corvina (Argyrosomus regius), un esciénido de características similares al verrugato, Ribeiro et al (2015) estudiaron el efecto de las dietas basadas en vegetales sobre el crecimiento, los parámetros intestinales y los indicadores de estrés hematológico durante 88 d y encontraron que el crecimiento de la corvina no se vio afectado significativamente por el formulate feeds.…”
unclassified
“…Reproduction without hormonal induction has already been achieved for shi drum born in captivity (Arizcun-Arizcun et al 2014). So far, some studies on its nutritional requirements (Akpinar et al 2012, Morgane and Fountoulaki 2014, Sevgili et al 2015 and on the use of plant sources (soybean and cereals) in its diet (Segato et al 2005(Segato et al , 2008 have showed that the shi drum can tolerate a relatively high inclusion of plant products without having negative effects on growth and feed efficiency. For juvenile meagre (Argyrosomus regius), a sciaenid with similar characteristics to the shi drum, Ribeiro et al (2015) studied the effect of vegetable-based diets on growth, intestinal parameters, and hematological stress indicators over a period of 88 d and found that growth was not significantly affected by the replacement of fish meal and fish oil with the alternative ingredients.…”
mentioning
confidence: 99%
“…Ya se ha logrado la reproducción, sin inducción hormonal, de ejemplares de esta especie nacidos en cautividad (Arizcun et al 2014). Hasta ahora, algunos estudios sobre sus necesidades nutricionales (Akpinar et al 2012, Morgane y Fountoulaki 2014, Sevgili et al 2015 y sobre el uso de fuentes vegetales (productos de soya y cereales) en su dieta (Segato et al 2005(Segato et al , 2008 han demostrado que el verrugato tolera una inclusión relativamente alta de productos vegetales sin tener efectos negativos en el crecimiento y la eficiencia alimenticia. En juveniles de corvina (Argyrosomus regius), un esciénido de características similares al verrugato, Ribeiro et al (2015) estudiaron el efecto de las dietas basadas en vegetales sobre el crecimiento, los parámetros intestinales y los indicadores de estrés hematológico durante 88 d y encontraron que el crecimiento de la corvina no se vio afectado significativamente por el formulate feeds.…”
unclassified